THE FIRST REPORT OF PESTALOTIOPSIS SP. CAUSING CROWN ROT DISEASE ON STRAWBERRIES IN DALAT - Lê Dũng; Nguyễn Thị Diên; Phan Hoàng Đại; Phạm Ngọc Tuân (Tạp chí Khoa học Đại học Đà Lạt)
Study on the pathogens causing strawberries crown rot disease was complied with the methodology of Koch. Results from isolating 150 samples of infected plant parts collected from three strawberry cultivated areas in Dalat (Ward 7, Ward 8 and Ward 12) indicated that there were 327 isolates belonging to six fungal species. Most fungi isolated from infected parts were identified as Botrytis cinerea, Verticillium sp., Cylindrocarpon destructans, Fusarium oxysporum, Rhizoctonia sp. and Pestalotiopsis sp., in which the main fungi consistently isolated were Pestalotiopsis sp.. By fulfilling Koch’s postulates, the results of pathogenesis test indicated that Pestalotiopsis sp. was a pathogen causing the crown rot disease on strawberries in Dalat. This is the first report on the association of Pestalotiopsis sp. with crown rot disease of strawberries in Vietnam.